A new species of Codinaea (Chaetosphaeriaceae, Sordariomycetes) from Taiwan - Kuo, Chang-Hsin; Hsieh, Sung-Yuan; Goh, Teik-Khiang (Phytotaxa, 2024)
Codinaea fecunda sp. nov. from decaying wood submerged in a freshwater stream in Fuxing District of Taiwan, is described and illustrated. It differs from other Codinaea species in having distinct tufts of long conidiophores that bear numerous phialides along the shafts. Its novelty is confirmed by phylogeny inferred by a concatenated dataset of the ITS, LSU, and TEF1-α sequences among the other 25 isolates of Codinaea species in the Chaetosphaeriaceae. A synopsis of the 79 Codinaea names in Index Fungorum is given, providing information regarding their nomenclatural changes, synonyms, and referencing articles.